Dairy and Cheese Production, Municipality of Paipa in The Context of “Food Security" - Acuña-Rodríguez, Olga Yanet; Acuña-Rodríguez, Blanca Ofelia; Cobo-Mejía, Elisa Andrea; Pinzón-Camargo, Libia Carolina; Albesiano-Fernández, Luis Enrique (Sociedad y Economía, 2022)
The article analyzes the implications of food security policies for dairy and cheese farmers in the municipality of Paipa (Colombia), during the period 2000-2010. These policies were disassociated from the Washington Meeting that defined strategies and guidelines on economic management for Latin America. Through this case study, from the perspective of social history, and under the concept of security as proposed by Foucault, we intend to establish the impact of this neoliberal macroeconomic policy on the daily life of farmers. This study has allowed us to understand how the Colombian peasant sector has gradually seen its economy decimated, while the large dairy producers, who have taken control of the production and trade of milk and cheese in Paipa, have become stronger. This situation is not unfamiliar to the experiences of Colombian peasants.